Proposed use of TinkerCad in primary school computer science classes to support Arduino programming - Kanta, Róbert; Takáčová, Andrea (International Journal of Advanced Natural Sciences and Engineering Researches, 2023)
– Nowadays, there is a strong emphasis on practical teaching, on teaching with the possibility ofusing what has been learned in the home environment or in leisure activities. This also requires the use ofmodern educational methods and, above all, modern teaching aids. This includes the TinkerCadenvironment accessible via a web interface. It allows not only full-fledged simulation but also the creationof your own program whether with deeper programming knowledge or just basic. Its great advantage isthat it is freely accessible and without any large financial outlay spent on buying an Arduino board orother electronic components, it allows you to develop your own simpler and more complex projects.These can also be developed by pupils in teams, thus encouraging pupils to work collectively. Last butnot least, we can also mention that using the simulation environment does not risk damaging theequipment and there is no risk of electric shock. Many pupils are very lively and interested in manythings, and they can also accidentally damage equipment. In our work, we will focus on the design ofsuch a project, where the Arduino calculates the product and sum from the two variables loaded. This willteach students how to use Arduino, LCD display, serial port with the aim of course to promotealgorithmic thinking and increase interest in science among students. By managing all this withoutprogramming in a commonly used programming environment, it allows us to use this example in theupper primary school years, where pupils can use their existing knowledge creatively.